Endorphins: "opiates for the masses". - Grossman, A (1985)
Endogenous opioid peptides rose to prominence with the discovery of the enkephalins in 1975. Since then, a vast amount of research has been directed toward understanding their role in normal and pathophysiological situations. Although the place of endogenous opioids in psychiatry remains uncertain, there is good evidence that a variety of tumors may secrete endorphins or enkephalins, and these may contribute to the non-metastatic complications of malignant disease. In addition, changes in cerebrospinal fluid met-enkephalin and beta-endorphin after acupuncture may be involved in the effectiveness of this therapy in the treatment of heroin withdrawal and severe pain. The hormonal effects of opiate agonists and antagonists are now well characterized; exercise-induced changes in circulating catecholamines are markedly enhanced by the opiate antagonist naloxone. It is possible that the opiate inhibition of catecholamine release during exercise is a reflection of endogenous opioid modulation of effort perception.